Autocorrelation and Linear Complexity of Binary Generalized Cyclotomic Sequences with Period pq - Yan Wang; Liantao Yan; Qing Tian; Liping Ding (Journal of Mathematics)
Ding constructed a new cyclotomic class V0 ,V1. Based on it, a construction of generalized cyclotomic binary sequences with period pq is described, and their autocorrelation value, linear complexity, and minimal polynomial are confirmed. The autocorrelation function CSw is 3-level if p≡3mod4, and CSw is 5-level if p≡1mod4. The linear complexity LCS>pq/2 if p≡1 mod 8, p>q+1, or p≡3mod4 or p≡−3mod8. The results show that these sequences have quite good cryptographic properties in the aspect of autocorrelation and linear complexity.